Power spectrum slope is related to motor function after focal cerebral ischemia in the rat. Issue 10 (24th August 2018) - Leemburg, Susan; Gao, Bo; Cam, Ertugrul; Sarnthein, Johannes; Bassetti, Claudio L
Abstract: Electroencephalography (EEG) changes across vigilance states have been observed after ischemic stroke in patients and experimental stroke models, but their relation to functional recovery remains unclear. Here, we evaluate motor function, as measured by single pellet reaching (SPR), as well as local EEG changes in nonrapid eye movement (NREM), rapid eye movement (REM), and wakefulness during a 30 day recovery period after middle cerebral artery occlusion or sham surgery in rats. Small cortical infarcts resulted in poor SPR performance and induced widespread changes in EEG spectra in the ipsilesional hemisphere in all vigilance states, without causing major changes in sleep–wake architecture. Ipsilesional 1–4 Hz power was increased after stroke, whereas power in higher frequencies was reduced, resulting in a steeper slope of the power spectrum. Microelectrode array analysis of ipsilesional M1 showed that these spectral changes were present on the microelectrode level throughout M1 and were not related to increased synchronization between electrodes. Spectrum slope was significantly correlated with poststroke motor function and may thus be a useful readout of recovery-related plasticity.